2022
DOI: 10.1039/d2cc00836j
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of presumed small-molecule ligands of telomeric i-DNA by biolayer interferometry (BLI)

Abstract: Biolayer Interferometry (BLI) and circular dichroism (CD) spectroscopies were used to investigate the interaction between previously reported i-motif DNA (i-DNA) ligands and folded or unfolded i-DNA in acidic (pH 5.5)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Indeed, a weak affinity with HRAS and bcl-2 sequences was observed while no recognition was detected with sequences HTelo-C and c-myc. The same behavior was already observed in our previous study using a panel of putative i-motif ligands which were found to not discriminate between folded and unfolded i-motif structures [18]. In summary, the results of BLI measurements indicate weak binding of IMC-48 to bcl-2 and HRAS sequences, both in acidic (favoring i-DNA) and neutral (disfavoring i-DNA) conditions, and the absence of interaction with HTelo-C and c-myc sequences, and they speak against a structure-selective binding to i-motifs.…”
Section: Evaluation By Bli Of the Affinity Of Imc-48 For Dna Sequencessupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, a weak affinity with HRAS and bcl-2 sequences was observed while no recognition was detected with sequences HTelo-C and c-myc. The same behavior was already observed in our previous study using a panel of putative i-motif ligands which were found to not discriminate between folded and unfolded i-motif structures [18]. In summary, the results of BLI measurements indicate weak binding of IMC-48 to bcl-2 and HRAS sequences, both in acidic (favoring i-DNA) and neutral (disfavoring i-DNA) conditions, and the absence of interaction with HTelo-C and c-myc sequences, and they speak against a structure-selective binding to i-motifs.…”
Section: Evaluation By Bli Of the Affinity Of Imc-48 For Dna Sequencessupporting
confidence: 87%
“…To address this controversy, in a recent study, we have investigated the interaction of these previously reported i-DNA “ligands” with folded or unfolded i-DNA in acidic (pH 5.5) and near-neutral (pH 6.5) conditions, respectively. We have demonstrated that most of them do not display a selective interaction with the i-DNA structure nor are able to promote its formation [ 18 ]. Likewise, Gargallo and coll.…”
Section: Introductionmentioning
confidence: 99%
“…When the pH value was changed from 7.4 to 5.6, negative CD peaks near 245 nm and positive CD peaks near 275 nm red-shifted to near 260 and 290 nm, respectively, revealing that the reduced pH value could promote the folding of the hairpin-contained i-motif quadruplex structure while the increased pH would facilitate the unfolding of the i-motif. [27][28][29] These phenomena clearly proved that the pH-guided allostery of the hairpin-contained i-motif on pH-Apt-YNA was good in line with our intention of design, and the nanoantenna could receive the changes of external pH and realize signal conversion effectively.…”
Section: Resultssupporting
confidence: 61%
“…In acidic conditions, hemi-protonated cytosine–cytosine base pairs (C–C + ) can generate a tetraplex structure known as the IM in cytosine-enriched DNA sequences. This structure contains two broad and two narrow grooves, as well as its C–C + plane is shorter than that of G4′s G-quartet . Even so, there are evidences for the generation of IMs at neutral pHs under supercoiling situations, molecular crowding circumstances, and in the presence of interacting molecules and cations. Furthermore, the growing number of IM interacting molecules has offered new opportunities for investigation into its biological roles and detection in human cell nuclei.…”
Section: Introductionmentioning
confidence: 99%